2016
DOI: 10.1111/jnu.12247
|View full text |Cite
|
Sign up to set email alerts
|

Resident‐Centered Care in 10 U.S. Nursing Homes: Residents’ Perspectives

Abstract: Purpose With increased focus on resident‐centered care (RCC) as an organizational imperative and a guiding principle of culture change for long‐term care communities, evaluation of its success has centered primarily on the organizational perspective. Methods For this case report, we examine resident perspectives of RCC in 10 nursing homes across the United States that had adopted RCC as a philosophy and model of care for at least 12 months with a maximum engagement of 3 years using a phenomenological approach.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 20 publications
(26 reference statements)
2
41
0
Order By: Relevance
“…Previous studies have emphasized the importance of empowering the direct care worker as one of the core components of any CC initiative. Although some studies found an association between staff empowerment and positive resident outcomes (Harrison & Frampton, 2017;White-Chu, Graves, Godfrey, Bonner, & Sloane, 2009), others have shown that empowering direct care staff increases staff satisfaction and retention (Berridge, Tyler, & Miller, 2018;Bowers & Nolet, 2011). For example, providing direct care workers with power and autonomy to make decisions increases satisfaction and feeling of empowerment among Shahbazim/CNAs in the Green House model (Bowers & Nolet, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have emphasized the importance of empowering the direct care worker as one of the core components of any CC initiative. Although some studies found an association between staff empowerment and positive resident outcomes (Harrison & Frampton, 2017;White-Chu, Graves, Godfrey, Bonner, & Sloane, 2009), others have shown that empowering direct care staff increases staff satisfaction and retention (Berridge, Tyler, & Miller, 2018;Bowers & Nolet, 2011). For example, providing direct care workers with power and autonomy to make decisions increases satisfaction and feeling of empowerment among Shahbazim/CNAs in the Green House model (Bowers & Nolet, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, building trust and promoting the maintenance of daily life functions after facility admittance are necessary. Since the late 1990s, resident-centered care, in which preferential value is placed on the choices of the elderly residing in an elderly-care facility and the philosophy and belief in creating a home-like atmosphere, has emerged [6,7]. Various terms are used to define this shift toward providing home-like nursing homes that are receptive to residents’ preferences, such as person- or resident-centered care [6].…”
Section: Introductionmentioning
confidence: 99%
“…Since the late 1990s, resident-centered care, in which preferential value is placed on the choices of the elderly residing in an elderly-care facility and the philosophy and belief in creating a home-like atmosphere, has emerged [6,7]. Various terms are used to define this shift toward providing home-like nursing homes that are receptive to residents’ preferences, such as person- or resident-centered care [6]. In addition, the terms refer to a collection of principles for nursing homes, including a relationship-based model of care, resident direction of his/her lifestyle, stability in staff who support residents, design of the physical space, and other foundations that contribute and define the quality of life on a personalized basis in nursing homes [6,7].…”
Section: Introductionmentioning
confidence: 99%
“… 13 Many long-term care facilities operate using the traditional medical model where people are often medicalised, subjected to ageism and have little or no power and control over their lives. 15 16 …”
Section: Introductionmentioning
confidence: 99%